ENERGI, MAKRONUTRIEN, DAN CAROTID INTIMA-MEDIA THICKNESS (CIMT) PADA REMAJA OBESITAS [Energy, Macronutrients, and Carotid Intima-Media Thickness (CIMT) in Obese Adolescents] - Nur Aisiyah Widjaja; Roedi Irawan; Meity Ardiana; Meta Herdiana Hanindita; Rendi Aji Prihaningtyas (Media Gizi Indonesia, 2020)
Obesity prevalence is increasing in adolescents. Subclinical chronic infl ammation in obesity causes complication, such as atherosclerosis. Cardiovascular disease is one of the complications of obesity that causes premature death. Carotid intima-media thickness (CIMT) is a subclinical marker of atherosclerosis which easily performed and noninvasive. Early detection of atherosclerosis can improved outcome. Healthy diet have a negative correlation with CIMT meanwhile high calori diet increase CIMT. This study aimed to examine the eff ect of energy and macronutrients intake on CIMT in obese adolescents. A cross sectional study was conducted on 59 adolescents aged 13-16 years old with obesity in pediatric clinic of Dr. Soetomo General Hospital using consecutive sampling method. Dietary intake was obtained through 1 x 24 hours food recall. Anthropometric measurements include body height and weight. Body Mass Index (BMI) was calculated. Obesity is defi ned as BMI higher than 95th percentile based on age and gender (CDC 2000 curve). CIMT examination was performed using B mode ultrasonography on the neck. Statistical analysis was perfomed using mutiple linear regression to analyze the eff ect of total energy, fat, and carbohydrate on CIMT. There were 59 obese adolescents included in this study, consist of 27 (45.8%) female adolescents and 32 (54.2%) male adolescents. No eff ects of total energy, carbohydrate, and fat on CIMT was found in obese adolescents (p>0.05). Further research with more subjects and at least 2x24 hours food recall are needed to assess the eff ect of calories and macronutrients on CIMT in obese adolescents.